SCIENTIFIC RESEARCH ACTIVITY AS A CRUCIAL FACTOR IN THE PROFESSIONAL DEVELOPMENT OF FUTURE PERSONNEL (Scientific journal of the Fergana State University, 2025)
This article explores the tasks facing higher education institutions in shaping students' scientific research competencies, the existing shortcomings in engaging students in research activities, and the significance of involving them in scientific research for their professional development. It analyzes the practical possibilities for further supporting scientific research activities in the context of the new Uzbekistan and the processes of establishing the Third Renaissance, as well as enhancing the integration of "science-education-production" in every sphere of society.